FROM THEORY TO PRACTICE: SYSTEMIC BARRIERS TO INTERNSHIP PARTICIPATION AND GRADUATE EMPLOYABILITY IN CAMEROONIAN HIGHER EDUCATION (American Journal of Pedagogical and Educational Research, 2026)
Despite the widespread implementation of the Bachelor-Master-Doctorate (BMD) system in Cameroon designed to definitively professionalize higher education a profound paradox persists: exponential graduation rates are met with escalating graduate underemployment. While corporate discourse frequently attributes this to a "skills mismatch," this narrative obscures a deeper, systemic denial of Work-Integrated Learning (WIL).